Investigating the Roles of Implicit and Explicit Knowledge in the Production of Grammatical Errors - Murniati Murniati (Journal of English Language and Culture, 2021)
This research aims to investigate the role of implicit and/or explicit knowledge in the production of grammatical errors in academic texts. Explicit knowledge is defined as conscious and declarative knowledge used to monitor language production while implicit knowledge is defined as an intuitive knowledge which enables the second language learners to use the language spontaneously without any reflection (Zhang, 2015). The reasons why this research is conducted is due to the fact that the students are still producing errors even though they have learnt English since elementary school. The data is gained from the academic text written down by fifteen English department students studying in a university in Jakarta. It is analyzed by using two different measurements: (1) Delayed Grammatical Judgment Tests (GJT), and (2) Interview including Metalingual Comment to investigate the role of explicit knowledge in the production of grammatical errors. The other two measurements are also used; they are (1) Timed Grammaticality Judgment Test (TGJT), and (2) Oral Production Test (OPT) to investigate the role of implicit knowledge. The results show that 19.2% of grammatical errors are produced due to the implicit knowledge and 80.8% is due to explicit knowledge. Since the explicit knowledge plays an important role in producing the grammatical errors, it can be concluded that teaching English grammar for university students is still important. If possible, the English Grammar lessons should be given more rooms in the overall curriculum